Attitude Assessment Methods and Instruments in Learning Evaluation - Yaqin, Muhammad; Yasin , Nur Ali (PT Ilmu Inovasi Nusantara, 2024)
This research aims to examine attitude assessment in the learning context, with a focus on Islamic Religious Education. Attitude is defined as a person's feelings, views, or tendencies in responding to objects or situations, which include three main components: affective, cognitive, and conative. These components shape attitudes towards subject matter, teachers, and the learning process as a whole. Attitude assessments are carried out to understand students' behavioral tendencies in learning, including positive attitudes towards material, teachers and a supportive learning environment. The research used a qualitative approach with a case study design, involving classroom observations, interviews with teachers and students, as well as analysis of related documents. The research results show that students' attitudes can be influenced by affective (emotion), cognitive (understanding) and conative (behavior) aspects. This research also developed an instrument to measure attitudes, which was designed to reflect objective and systematic assessment standards. These findings provide practical insight for educators in evaluating and forming students' attitudes in a comprehensive and accountable manner, supporting successful learning and the development of students' character.